(untitled) (Indian Journal of Public Health Research & Development, 2020)
The purpose of this study is to compare women with major depression against their matched healthy controls about their coping mechanisms and the severity of their symptom condition. Method: This cross-sectional hospital-based survey recruited 37 women with major depression and 40 non-depressed women as healthy controls. Simple random sampling was used to select the participants. Data was collected by using self-reported tools. Descriptive statistics and interpretative analysis of data was performed by using independent-samples t-test, ANOVA, and post hoc Tukey HSD multiple comparison tests to find out the accurate differences between levels of depression. The results show that women who used more self-blame, rumination bordering on to brooding, and less positive reframing had higher levels of depressive symptoms. Among the positive coping mechanisms, it was noted that in the clinical sample used instrumental and emotional supports. With regard to negative strategies for coping depression, self-blame, self-distraction, denial and venting were common. The use or non-use of a given coping mechanisms varied with the severity of depression. Conclusion: The study concludes that women with major depression use qualitatively different coping mechanisms for coping depression than healthy controls. This has implications for planning psychotherapeutic programs for the affected women.